1997
DOI: 10.1046/j.1570-7458.1997.00179.x
|View full text |Cite
|
Sign up to set email alerts
|

Dropping of pea aphids from feeding site: a consequence of parasitism by the wasp, Monoctonus paulensis

Abstract: We examined the dropping behaviour of the pea aphid, Acyrthosiphon pisum (Harris), feeding on broad‐bean plants in the laboratory. Aphid responses to foraging and oviposition by females of Monoctonus paulensis (Ashmead) were instar‐specific and included kicking with the hind legs, walking away and dropping from the feeding site. Fourth nymphal instars were most likely to drop, followed by second, third, and first instars, in that order. Compared with first instars, the odds that a fourth‐instar aphid will drop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 21 publications
0
58
0
Order By: Relevance
“…Third, we tested the hypothesis that parasitoid prefer ence reflects differences in handling costs and oviposition success between host types (Iwasa et al, 1984;Gerling et al, 1990;Chau & Mackauer, 1997;Losey & Denno, 1998). Anti-parasitoid behaviour including dropping from the feeding site and kicking with the hind legs are gener ally better developed in older instars and adult aphids than in first instars.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Third, we tested the hypothesis that parasitoid prefer ence reflects differences in handling costs and oviposition success between host types (Iwasa et al, 1984;Gerling et al, 1990;Chau & Mackauer, 1997;Losey & Denno, 1998). Anti-parasitoid behaviour including dropping from the feeding site and kicking with the hind legs are gener ally better developed in older instars and adult aphids than in first instars.…”
Section: Discussionmentioning
confidence: 99%
“…Anecdotal observations by Calvert & van den Bosch (1972b) and Calvert (1973) suggest that M. paulensis selectively parasitizes small first and second nymphal instars, as was also observed by Griffiths (1960) in Monoctonus crepidis (Haliday). Chau & Mackauer (1997) provided a possible explanation of this apparent preference for small rather than large hosts. They showed that parasitoid offspring were most likely to survive in first instars of the pea aphid, which had the lowest mor tality risk due to dropping from the feeding site after parasitism as compared with other instars.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Typical responses range from the cessation of feeding and removal of the stylet from host plant tissues to walking, jumping, or falling away from the source of emission (Edwards et al, 1973;Wientjens et al, 1973;Phelan et al, 1976;Nault, 1977a, b, 1978;Roitberg and Myers, 1978;Wohlers, 1980;Clegg and Barlow, 1982;Chau and Mackauer, 1997;Losey and Denno, 1998;Shah et al, 1999;Braendle and Weisser, 2001). In the sugar-cane woolly aphid, Ceratovacuna lanigera Zehntner (Homoptera, Pemphigidae), the alarm pheromone reportedly elicited aggressive behavior from conspecifics (Arakaki, 1989).…”
Section: Figure 1 Near Herementioning
confidence: 99%